Kajian Penerapan CHSE pada Wisata Berkemah di Umbul Sidomukti, Kabupaten Semarang - Renesia Nur Rachma Ayu Lisanti; Maya Damayanti (Jurusan Perencanaan Wilayah dan Kota, 2023)
The tourism sector is one of the affected economic sectors due to the COVID-19 pandemic, including Indonesia. Therefore, The Indonesian Government offered ways to recover tourism sector activities regarding its impact by applying the health protocol released by Kemenparekraf (Ministry of Tourism and Creative Economy of the Republic of Indonesia), based on CHSE (Cleanliness, Health, Safety, and Environment Sustainability). This study is located in the camping destination in Umbul Sidomukti, Semarang Regency. This study aims to identify the health protocol applied in camping destination in Umbul Sidomukti. Regarding its aim, quantitative descriptive is used by collecting data through interviews and observations. The study results showed that the camping destination in Umbul Sidomukti already applies the health protocol based on the policy. Tourists are also obey the health and safety protocol at the camping destination. This result is related to the changes in tourists’ behaviour due to pandemic COVID-19 in general.